TRANSFER PROBLEMS IN PUBLIC ADMINISTRATION OF UKRAINE - Устинова, Ірина Петрівна; Яківчук, Жанна Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
The purpose: the main task on the road to improving economic, social and other equally important indicators in the state is to create an effective mechanism for the functioning of public authorities. Public administration is a central element of a well-functioning and effective life of a society. The presence of such a phenomenon contributes to the high-quality implementation of the powers entrusted to them by all civil servants. Decentralization has been introduced to improve the functioning and implementation of relevant tasks, but proposals for its improvement are still needed. That is why it is expedient to study these phenomena as separate, as well as in connection with budgetary processes as inherent to each society. This topic of research is relevant primarily because public administration and decentralization are directly related to intergovernmental regulation and the involvement of various transfers in the form of subventions. The purpose of the study is to analyze the results of the public administration and the changes after the introduction of decentralization; studying the prospects of attracting intergovernmental transfers and their relationship with public administration. Results: the authors argue that the efficient functioning of public administrations depends on financial legal relationships and the introduction of such phenomena as decentralization. To ensure well-established links between executive authorities and financial bodies, it is necessary to develop an effective mechanism that would work to obtain funds for the benefit of individual regions. It is also necessary to coordinate actions of national and local authorities in order to faithfully carry out their duties and improve the overall picture of budget implementation. By introducing such a phenomenon as decentralization, Ukraine has a real opportunity to save received funds in the local budget and thus direct them for a new appointment, taking into account the needs of the population of a particular region. Methods: comparative-legal, sociological, dialectical, method of synthesis. according to the results of the study, the main advantages of public administration were identified, the introduction of such a phenomenon as decentralization and the use of intergovernmental transfers.